O infográfico e a divulgação científica midiática (DCM): (entre) texto e discurso - Souza, Juliana Alles de Camargo de (Universidade do Vale do Rio dos Sinos, 2012)
Infographics have been largely used in several communicative situations that involve different knowledge areas, especially in the media domain. In the context of the Divulgation of Science in the Media (DSM), the infographic that contemplates the dimensions of the know-how and of the make-comprehend science, marked by the make-feel promoted by the plasticity of the colors, shapes and topography used in the diagram is highlighted. To the best of our knowledge, there are few studies about this syncretic text (in which image and word, simultaneously, produce the comprehension). Consequently, since the beginning of this research only studies in the field of journalism were found, related to Communication Sciences. For this reason, this thesis aims at investigating the infographic from a discursive-linguistic point of view based on the Semiolinguistic and Textual Linguistics theories supplemented by epistemic contributions of the Plastic Semiotics. The latter enables the analysis of the image and integrates the Linguistics perspective focused in this ancestral and contemporary text of the human communication. Specifically, the main aim of this study is to analyze what is the configuration of the processes that constitute the linguistic organization of the infographics taking into consideration that the mechanisms of the verbal and visual language point to descriptive, narrative and explanatory actions. As part of the methodological path, the first step was the collection of a corpus of 58 infographic texts, isolated or inserted in longer articles of scientific divulgation magazines in the media such as “Superinteressante”, “Saúde! é vital” and “Mundo Estranho”. The texts were selected between August 2008 and December 2009. In a second step, an analysis of the discursive-textual aspects of each infographic was performed, compounding an annotation table that was reviewed each semester during the thesis development period. From this observation and using these procedures, different theories that can clarify the composition of the DSM infographic were elaborated, which implies in assuming the qualitative characteristic of the methodology. The following results were noted: the DSM infographic reveals itself as a descriptive tool in the verbal dimension as well as in the visual dimension. Such descriptive feature enables the anchorage of narrative actions (to a lesser extent) and creates the possibility of explanations, in a greater number of the texts analyzed, about phenomena, objects and facts, both in explanatory sequences and in ilocutory aims of texts, related to science or technology. Consequently, infographics have an important role in complex explanations, as verbal and visual aspects promote an informative optimization (make-know and make-comprehend). In conclusion, it is possible to classifiy the in fographic as a relevant text of the verbal, scientific and visual literacy. Furthermore, it carries out that researches about this form of producing comprehension in a text are significant for educational actions, foreseen in the “Parâmetros Curriculares Nacionais” (PCNs) and in literacy projects or programs in several areas of the human knowledge.
Keywords: Discurso e texto; Infográfico; Sincretismo; Descrição; Narração; Explicação; Discourse and text; Infographic; Syncretism; Description; Narrative; Explanation; ACCNPQ::Lingüística, Letras e Artes::Lingüística